SERVICE QUALITY AND NET PROMOTE SCORE (NPS): A LITERATURE REVIEW ON THEIR RELATIONSHIP IN HEALTHCARE SERVICE - Lombongkaehe, Citra Marianti Ningsih; Grace Solely Houghty (Jurnal Penelitian Keperawatan Kontemporer, 2025)
This literature review examines the relationship between service quality and Net Promoter Score (NPS) in the context of Indonesian healthcare services. Drawing on recent empirical studies, the review highlights that improvements across all dimensions of service quality-tangibility, reliability, responsiveness, assurance, and empathy-are essential for achieving high patient satisfaction and fostering loyalty. The findings indicate that while NPS is a useful and increasingly popular metric for measuring patient loyalty, its effectiveness is limited if used in isolation, as it may not fully capture the complexity of patient experiences and can be influenced by contextual factors. Therefore, integrating NPS with comprehensive service quality assessments and qualitative feedback is recommended to provide a more accurate and actionable understanding of patient perceptions. This review offers practical guidance for hospital managers seeking to enhance both patient experience and organizational performance through a holistic approach to service quality improvement.